Deteksi Dini dan Intervensi Aneurisma Aorta Abdominalis Sakular dengan Hematoma Intramural - Ary Kurniawan; Kurnianingsih Kurnianingsih (RSUD Dr. Saiful Anwar Province of East Java, 2026)
Background: Saccular Abdominal Aortic Aneurysm with intramural hematoma carries a high risk of rupture, often presenting with atypical clinical manifestations that lead to delayed diagnosis. Case Illustration: A 68-year-old male presented with progressive abdominal pain over 4 months, diagnosed as gastritis. After 3 months without improvement, subsequently duplex ultrasonography and CT-Angiography confirmed a saccular AAA with intramural hematoma. The patient underwent EVAR with Stent Graft implantation. Case Discussion: This case highlights the diagnostic challenges of atypical AAA presentation, the importance of appropriate vascular imaging, and the significance of saccular morphology and intramural hematoma as high-risk factors for rupture. EVAR was selected for its lower perioperative mortality and morbidity compared to open surgery. Conclusion: Clinical vigilance for atypical AAA presentations, appropriate diagnostic imaging, and early endovascular intervention enable optimal management of this potentially fatal vascular condition.